2020
DOI: 10.1155/2020/4039134
|View full text |Cite
|
Sign up to set email alerts
|

Field‐Obtained Soil‐Water Characteristic Curves of KPK Expansive Soil and Their Prediction Correlations

Abstract: Expansive clays are found worldwide in arid and semiarid regions. Such soils are considered a natural hazard for civil engineering infrastructures especially when they are lightly loaded. Expansive soils are often unsaturated due to the high absorption capacity of moisture. The damaging effect of expansive soils is intimately related to the distinctive soil-water characteristic in the surficial soil layers subjected to wetting-drying cycles. The soil-water characteristic curve (SWCC) also known as the water-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…SM is low in Baluchistan due to late summer droughts that stress the SM by increasing the evapotranspiration process [ 77 ]. Zamin et al [ 85 ] conducted a study in which they reported that swelled and expansive soil followed by desiccation cracks are found in the region of Kohat, Bannu, and Dera Ismail Khan of Khyber Pakhtunkhwa.…”
Section: Resultsmentioning
confidence: 99%
“…SM is low in Baluchistan due to late summer droughts that stress the SM by increasing the evapotranspiration process [ 77 ]. Zamin et al [ 85 ] conducted a study in which they reported that swelled and expansive soil followed by desiccation cracks are found in the region of Kohat, Bannu, and Dera Ismail Khan of Khyber Pakhtunkhwa.…”
Section: Resultsmentioning
confidence: 99%
“…The arid climate and severe weathering conditions intensify the presence of such soils [8]. In Pakistan swelling clay of low and high plasticity are also reported in the Karak, Bunnu, Kohat, DI Khan, and Jhelum areas [9]. The presence of expansive soils can be assumed from several visual indicators like desiccation cracks on the natural surface ground, diagonal crack, and sinking of lightly loaded structures in the surrounding areas.…”
Section: Introductionmentioning
confidence: 99%
“…Khan, Dera Ismail (D.I.) Khan, and so many other places as well [6] and have damaged many structures.…”
Section: Presence Of Expansive Soilsmentioning
confidence: 99%
“…e problems associated with foundations on expansive soils incorporate heaving, breaking, and cracking of the superstructure. It also produces distress in pavements, slab-on-grade members, channels, and reservoir linings [6].…”
Section: Associated Problems and Mechanismmentioning
confidence: 99%